Second-Order Containment Control of Multiagent Systems in the Presence of Uncertain Topologies with Time-Varying Delays - Fuyong Wang; Hongyong Yang; Zhongxin Liu; Zengqiang Chen (Journal of Control Science and Engineering)
This paper considers the containment control problem of second-order multiagent systems in the presence of time-varying delays and uncertainties with dynamically switching communication topologies. Moreover, the control algorithm is proposed for containment control, and the stability of the proposed containment control algorithm is studied with the aid of Lyapunov-Krasovskii function when the communication topology is jointly connected. Some sufficient conditions in terms of linear matrix inequalities (LMIs) are provided for second-order containment control with multiple stationary leaders. Finally, simulations are given to verify the effectiveness of the obtained theoretical results.